Heat accumulation in the network of efficient heat-and-cold supply system of a residential building - Stepanov, Dmytro; Stepanova, Nataliya; Gaydeychuk, Oleksandr (Scientific Works of Vinnytsia National Technical University, 2015)
The paper analyzes variants of operation of the heat-and-cold supply system for a residential building, which includes heat pumps and heat accumulators. Study of the influence of heat pump power on the storage tank volume and daily expenses for electric energy have been performed taking into account two- and three-zone electricity accounting system. Dependence of the heat storage tank volume for hot water supply system on hot water and cold supply power ratio has been obtained. Feasibility boundaries of implementing the cogeneration heat-an-cold supply systems in buildings are determined. REFERENCES 1. Амерханов Р. А. Тепловые насосы / Р. А. Амерханов. – М. : Энергоатомиздат, 2005. – 160 с. 2. Степанов Д. В. Вибір ефективного джерела теплохолодопостачання житлової будівлі / Д. В. Степанов, Н. Д. Степанова, О. А. Гайдейчук // Сучасні технології, матеріали і конструкції в будівництві. – 2013. – № 1. – С. 149 – 152. 3. Степанов Д. В. Ефективна система теплохолодопостачання житлової будівлі / Д. В. Степанов, Н. Д. Степанова, О. А. Гайдейчук // Сучасні технології, матеріали і конструкції в будівництві. – 2014. – № 2. – С. 151 – 154. 4. Постанова НКРЕКП про внесення змін до Порядку застосування тарифів на електроенергію. Зареєстрована 02.02.2015. [Електронний ресурс] / Режим доступу: http://zakon2.rada.gov.ua/laws/show/z0236-15. 5. Степанов Д. В. Суміщення теплохолодильних машин та електронагрівника в схемі джерела теплохолодопостачання. / Д. В. Степанов, Н. Д. Степанова, А. А. Керн //Енергетика та електрифікація. – 2011. – № 6. – С. 49 – 53. 6. Пуховий І. І. Акумулятори холоду з використанням фазового переходу. / І. І. Пуховий, М. О. Кривошеєв // Вісник ВПІ. – 2013. – № 1. – С. 74 – 79.